2018
DOI: 10.1515/johh-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temporal averaging of meteorological data on predictions of groundwater recharge

Abstract: Accurate estimates of infiltration and groundwater recharge are critical for many hydrologic, agricultural and environmental applications. Anticipated climate change in many regions of the world, especially in tropical areas, is expected to increase the frequency of high-intensity, short-duration precipitation events, which in turn will affect the groundwater recharge rate. Estimates of recharge are often obtained using monthly or even annually averaged meteorological time series data. In this study we employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The episodic nature of recharge, reported in the literature (e.g., Hunt et al, 2008;Smerdon et al, 2008), is lost when precipitation values are averaged over longer time periods. Similar conclusions on the influence of time averaging of the weather data were also presented by Batalha et al (2018). These authors found that using long-term averages of precipitation and evapotranspiration will lead to severe underestimates of the recharge rates as compared to the use of daily data.…”
Section: Influence Of the Temporal Resolution Of Weather Datasupporting
confidence: 71%
See 1 more Smart Citation
“…The episodic nature of recharge, reported in the literature (e.g., Hunt et al, 2008;Smerdon et al, 2008), is lost when precipitation values are averaged over longer time periods. Similar conclusions on the influence of time averaging of the weather data were also presented by Batalha et al (2018). These authors found that using long-term averages of precipitation and evapotranspiration will lead to severe underestimates of the recharge rates as compared to the use of daily data.…”
Section: Influence Of the Temporal Resolution Of Weather Datasupporting
confidence: 71%
“…Foussereau et al, 2001;Persson and Saifadeen, 2016;Vero et al, 2014), with results showing that using longer averaging periods (e.g., daily vs. hourly) of weather data leads to less recharge and longer solute travel times. A systematic study by Batalha et al (2018) evaluated groundwater recharge in different climatic regions of Brazil. They found that recharge rates calculated using daily climatological data were up to 9 times larger than those obtained using yearly averages.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, one obtains estimations of both water and solute fluxes at the water table on condition that detailed weather, soil and vegetation data are available as the model input. This approach is gaining increasing popularity; however, the results were shown to depend on many factors, including the time resolution of the weather data [16][17][18]. Recently, Vero et al [19] presented a comprehensive framework for estimating travel time based on simulations with the HYDRUS-1D computer code [20].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the groundwater level in Hebei plain of northern China has a declining rate of 1 to 2 m year −1 , with a total decline of 10 to 30 m over the past decades (Lu, Jin, van Genuchten, & Wang, 2011). Accordingly, there is a need to quantitatively assess the accuracy of the methods adopted to estimate groundwater recharge under intensive human activities and climate changes (Batalha, Barbosa, Faybishenko, & van Genuchten, 2018).…”
Section: Introductionmentioning
confidence: 99%